Η Διαφορετικότητα Βιολογίας και Φυσικής ως Διδακτικό Εργαλείο (και) στα Πλαίσια της STEM Διδασκαλίας - Αθανασίου, Κυριάκος (Πανελλήνιο Συνέδριο της Διδακτικής των Φυσικών Επιστημών και Νέων Τεχνολογιών στην Εκπαίδευση, 2025)
The paper is an attempt to constructively use the differences between Science, led by Physics, on one hand and Biology on the other. More specifically, the common framework of STEM teaching is encouraged as a teaching tool for teaching concepts related to the epistemology of the two disciplines, through their epistemological differences. As such disparities, the following are proposed: The existence of a unifying theory in their teaching, and the absence of "universal" laws in Biology. Furthermore, the dissimilar roles played among them by the experiment, mathematics and history. In addition, it is commended the difference in the meanings of the concepts "Social Implications" and "Social Science", together with the meaning of the essentialism in Physics, as opposed to the non-typological "population perspective" in Biology, where the endless, random errors and deviations (mutations) are the universal driving force, that prevails behind all biological phenomena.